2004
DOI: 10.1523/jneurosci.5112-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of HippocampalDe NovoProtein Synthesis and Actin Rearrangement in Extinction of Contextual Fear

Abstract: It is believed that de novo protein synthesis is fundamentally linked to synaptic changes in neuronal circuits involved in acquisition and extinction of conditioned responses. Recent studies show that neuronal plasticity may be also altered by cytoskeletal rearrangement independently of protein synthesis. We investigated the role of these processes in the hippocampus during acquisition and extinction of context-dependent conditioned fear in mice. Intrahippocampal injections of the protein synthesis inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
204
2
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 39 publications
15
204
2
1
Order By: Relevance
“…Two papers, both involving context fear extinction in mice, reported either no effect 316 (see also Lattal et al 327 ) or an apparent facilitation of extinction by ANI. 315 In the latter report, ANI infused into dorsal hippocampus immediately after the first of five daily extinction exposures to context produced a loss of context fear responses that persisted for several days even though ANI was discontinued. Although this sort of deficit is characteristic of a reconsolidation impairment, Fischer et al 315 argued that it actually was due to facilitated extinction because unsignaled shock exposure restored context freezing, similar to a reinstatement effect.…”
Section: Neurotransmitter Systemsmentioning
confidence: 88%
See 2 more Smart Citations
“…Two papers, both involving context fear extinction in mice, reported either no effect 316 (see also Lattal et al 327 ) or an apparent facilitation of extinction by ANI. 315 In the latter report, ANI infused into dorsal hippocampus immediately after the first of five daily extinction exposures to context produced a loss of context fear responses that persisted for several days even though ANI was discontinued. Although this sort of deficit is characteristic of a reconsolidation impairment, Fischer et al 315 argued that it actually was due to facilitated extinction because unsignaled shock exposure restored context freezing, similar to a reinstatement effect.…”
Section: Neurotransmitter Systemsmentioning
confidence: 88%
“…315 In the latter report, ANI infused into dorsal hippocampus immediately after the first of five daily extinction exposures to context produced a loss of context fear responses that persisted for several days even though ANI was discontinued. Although this sort of deficit is characteristic of a reconsolidation impairment, Fischer et al 315 argued that it actually was due to facilitated extinction because unsignaled shock exposure restored context freezing, similar to a reinstatement effect. However, the shock was given in a novel context, which would not be expected to produce reinstatement of extinguished fear because reinstatement is context specific.…”
Section: Neurotransmitter Systemsmentioning
confidence: 88%
See 1 more Smart Citation
“…β-actin is highly enriched in filopodia and spines (Bassell et al, 1998;Eom et al, 2003), and regulates the shape of dendritic spines and filopodia during development and structural plasticity at mature synapses (Fischer et al, 2004;Honkura et al, 2008;Krucker et al, 2000;Lamprecht and LeDoux, 2004;Matus, 2000;Okamoto et al, 2004;Sekino et al, 2007). The equilibrium between the filamentous form of actin (F-actin) and globular form (G-actin) is thought to be important for the regulation of the spine structure (Okamoto et al, 2004).…”
Section: Actin Polymerization Quantified With the Megfp-sreach Pairmentioning
confidence: 99%
“…A number of studies have shown that some, but not all, components of the molecular machinery that is required for the initial encoding of fear memories also regulate extinction 7-10 . Recent studies indicate that synaptic remodeling, for example, mediated by actin re-arrangement, may be important for extinction 3,6 . Actin dynamics are intimately involved in synaptic plasticity, synapse formation and neuronal morphology 6,11,12 .…”
mentioning
confidence: 99%